Analysis of Mathematical Reasoning Ability in Third Grade Elementary School Students - Sevian Ageng Wahono; Ihza Latifatun Ni'mah; Zahra Rahmawati; Neni Mariana; Vivi Astuti Nurlaily; Rheny Puspita Ratih (Universitas Negeri Surabaya, 2025)
Mathematical reasoning ability is a crucial competency to be developed at the elementary school level, as it enables students to understand concepts, connect ideas, and explain problem-solving processes logically. This study aims to analyze the mathematical reasoning abilities of third-grade elementary school students in the topic of length measurement using standard units. A mixed-methods survey design was employed, involving 10 third-grade students from Lidah Wetan State Elementary School, Surabaya. Data were collected through written tests, classroom observations, and teacher interviews. The assessment instrument was developed based on three indicators of mathematical reasoning: understanding basic concepts and procedures, connecting concepts through comparison and unit conversion, and explaining reasoning and solution steps. The findings reveal an average score of 69, categorized as good, although students’ abilities were uneven. Achievement levels across the three indicators reached 70 percent, 50 percent, and 40 percent, respectively. These results indicate that students’ mathematical reasoning remains predominantly procedural, highlighting the need for instructional practices that emphasize conceptual connections and logical justification.